2022
DOI: 10.1111/1759-7714.14345
|View full text |Cite
|
Sign up to set email alerts
|

Response to ALK‐TKIs in a lung adenocarcinoma patient harboring dual DCTN1‐ALK and ALK‐CLIP4 rearrangements

Abstract: Rearrangements involving anaplastic lymphoma kinase (ALK) gene have been reported in ~5% of non-small-cell lung cancer patients. These rearrangements are characterized by the identification of various rare fusion partners, with unknown clinical significance. Specifically, the concurrence of different ALK fusions within the same patient, as well as its impact on therapeutic response to ALK tyrosine kinase inhibitors (ALK-TKIs), are rarely reported. Here, we report a 46-year-old female who was diagnosed with lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This fusion has been seen to be recurrent in CAF in small studies. 13 The FN1::EGF fusion has only been observed in CAF and not in other types of neoplasms and small studies indicate it is the main driver mutation in CAF. 21 However, further functional studies need to be conducted to determine the mechanism of cancer onset in CAF tumors 21 and therefore it cannot yet be classified as a tier I fusion (see Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fusion has been seen to be recurrent in CAF in small studies. 13 The FN1::EGF fusion has only been observed in CAF and not in other types of neoplasms and small studies indicate it is the main driver mutation in CAF. 21 However, further functional studies need to be conducted to determine the mechanism of cancer onset in CAF tumors 21 and therefore it cannot yet be classified as a tier I fusion (see Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“… 6 Conversely, there remains continued debate about which fusion genes are of clinical value and are considered actionable, particularly when more than 1 fusion is discovered in a single tumor sample. 7 , 8 Several studies have demonstrated multiple fusions in single tumor samples, predominantly in hematopoietic 9 - 11 and epithelial 12 - 15 malignancies. While similar findings have been reported in soft tissue samples, 16 the incidence of multiple fusions in single PSTBT samples has not been well documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five patients developed ALK fusion, including a rare fusion type DCTN1/ALK (D24: A20). Gao Fangfang, et al (19) have reported that one case of DCTN1/ALK achieved partial response after receiving cabozantinib therapy. ERBB2, RET, ROS1, PIK3CA, BRAF, and NRAS were detected in older LUAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent presence of 2 or more ALK-fusion forms is rare. [2,3] Echinoderm microtubule-associated protein 4 (EML4) is the most frequently fusion partner of ALK fusion. [4] Additionally, brain metastasis occurs in approximately 23% to 31% of patients with ALK-fusion NSCLC and is associated with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%